Diagnostic Dilemmas: Overlapping Features of Brugada Syndrome and Arrhythmogenic Right Ventricular Cardiomyopathy - Hoogendijk, Mark (Frontiers in Physiology, 2012)
Arrhythmogenic right ventricular cardiomyopathy and Brugada syndrome are distinct clinical entities which diagnostic criteria exclude their coexistence in individual patients. Nonetheless, overlap in clinical features of these conditions have been recognized from the introduction of the Brugada syndrome. This review focuses on this overlap and discusses its consequences.